2006
DOI: 10.1159/000087456
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Movements and Breathing Patterns among Healthy Men and Women 20–69 Years of Age

Abstract: Background: Measurements in absolute terms of the whole respiratory movement pattern (range, type, symmetry, rhythm and frequency of breathing movements) of healthy individuals are valuable for reference, when assessing patients with conditions affecting respiration. Objective: To establish reference data for breathing movements and patterns for healthy men and women. Methods: Fifty men (mean age 47.8 years) and 50 women (mean age 43.4 years) aged between 20 and 69 years participated in the study. Anterior-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 30 publications
3
68
2
Order By: Relevance
“…Furthermore, there were also significant relationships between lower thoracic and abdominal movement and sex. Ragnarsdóttir and Kristinsdóttir 11 reported that abdominal, but not lower thoracic, movements were significantly less during deep breathing in females than in males. Verschakelen and Demedts 4 found that females exhibited slightly more rib cage movement during deep breathing.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there were also significant relationships between lower thoracic and abdominal movement and sex. Ragnarsdóttir and Kristinsdóttir 11 reported that abdominal, but not lower thoracic, movements were significantly less during deep breathing in females than in males. Verschakelen and Demedts 4 found that females exhibited slightly more rib cage movement during deep breathing.…”
Section: Discussionmentioning
confidence: 97%
“…Calcification of the costochondral cartilage and loss of elasticity of the connective tissue reduces the compliance of the thoracic cage. Reduction of lung compliance due to aging reduces chest expansion [12].…”
Section: Resultsmentioning
confidence: 99%
“…The lung volumes and capacities vary with the age, height, body surface area. Females have lesser average height and the body surface area than the males also the force generated by the Inspiratory muscles of males is greater than the females [12]. The difference in the chest expansion measurements can also be due to variable instructions given by the tester [12].…”
Section: Resultsmentioning
confidence: 99%
“…One group of authors, (27) investigating the respiratory movements and breathing patterns of men and women during normal deep breathing, found that there was less abdominal motion in the women, suggesting decreased diaphragmatic mobility in women under these conditions. Some authors have reported that women show 11-20% less diaphragmatic excursion during deep breathing, in comparison with men.…”
Section: Discussionmentioning
confidence: 99%